Implementation of Project-Based Learning (PjBL) Vocational High Schools (SMK) - Sulistyowati, Nur Wahyuning; Astuti, Elly; Wulandari, Meilinda Ike (Jurnal Manajemen Pendidikan, 2025)
Background The inconsistency in the implementation of the PjBL learning model for class X AKL SMK PGRI Wonoasri in the independent curriculum listed in the Decree of the Minister of Education and Culture of the Republic of Indonesia is the basis for this research. Intention This study aims to analyze how the implementation of PjBL class X AKL SMK PGRI Wonoasri in the independent curriculum. Design/method/approach This type of research is qualitative descriptive. Primary data is collected through documentation, observation, and interviews. Furthermore, data analysis is carried out by means of 1) collection, 2) reduction, 3) presentation, and 4) conclusion drawn. Result The research shows that the implementation of the independent Curriculum PjBL in class X AKL SMK PGRI Wonoasri is not in accordance with the PjBL of the independent Curriculum of the Ministry of Education and Culture. The PjBL learning model is a solution to address problems that occur in the field, both in the education sector and beyond. Contributions/values Research contributions include 1) adding insight for readers and authors regarding the implementation of PjBL learning for Vocational High School Department of Institutional Financial Accounting; 2) as a material for consideration, development, and evaluation by schools, teachers, and students in the implementation of the PjBL Learning model.